(untitled) (Journal of Philosophy, Culture and Political Science, 2021)
The paper considers culture as an important resource through which various changes in the urban environment are carried out. The analysis of the cultural realities of European cities covered in the Cultural and Creative Cities Monitor framework (CCCM) shows the presence and attractiveness of cultural institutions and places (cultural diversity) in the urban environment, the feature of culture to create jobs and innovation (creative economy), and conditions conducive to the flourishing of cultural and creative processes (favorable environment).The study results show cultural and creative values ​​are distributed differently in European cities, in this regard, local authorities are able to develop strategies taking into account specific features and conditions of each city. Particularly, it concludes that medium-sized cities cultural fund amount per capita exceeds the amount in large cities. Accordingly, the analysis carried out makes it possible to assess the level of development of urban culture at individual stages and determine its impact on the development of cities and population as a whole. However, the following questions remain: what cultural heritage, economic variables or institutional factors can explain the marked differences between cities? How can culture influence the economic environment of a city and the well-being of people in different typologies of cities? How do changes in the urban structure contribute to the development of cultural institutions and events? Do urban dwellers have the same opportunities to access culture and develop cognitive and relational skills within and outside the urban environment? The answers to these questions may influence to the research outcomes in the field of culture, urban planning, comparative public policy, etc. Key words: urban culture, cultural foundations, creative economy, cultural diversity, traditions and values.